Hubungan Dukungan Keluarga Dan Kepatuhan Minum Obat Pada Penderita Diabetes Mellitus Tipe II di Poliklinik Penyakit Dalam Rumah Sakit Umum Daerah 45 Kuningan - Belly Fariansyah; Dwi Putri Parendrawati; Abdal Rohim (Lembaga Penelitian Sekolah Tinggi Ilmu Kesehatan Kuningan, 2012)
Introduction: Diabetes mellitus is one of public health concern in the world, including in Indonesia. Based on Basic Health Research 2007, approximately 5.7% population in Indonesia was suffered diabetes mellitus, especially noninsulin dependent diabetes mellitus type. There are many complications due to diabetes mellitus such as macrovascular and microvascular complications. Therefore, diabetes mellitus patients should be treated and got medication regularly. This research aims to analyze the association between family’s supports with medication compliance among 2nd type diabetic patients in Internal Medicine Polyclinic 45 Kuningan General Hospital. Method: This study is designed by cross-sectional design. The samples is taken by purposive technique, with inclusion criteria: (1) less than 60 years age, (2) NIDDM type, (3) more than 1 time visit polyclinic. Data were collected by questionnaire and analyzed by Chi Square test. Results: The results show that 53.2% patients have a good support from their family members, 66% patients have a good compliance for medication, and there is a significant association between family support with medication compliance among 2nd type diabetic patients (p = 0.028; OR = 2.639). Discussion: Hospital management is recommended to develop a specific educational team serving diabetic patients and families and in addition, the nurse must also enhance their competencies, especially in implementing the therapeutic communication and health education.